Four views on hell - Sprinkle, Preston M., 1976- (Grand Rapids, Michigan : Zondervan, 2016)
Recent years have seen much controversy regarding hell: Do we go to heaven or hell when we die? Or do we cease to exist? Are believers and unbelievers ultimately saved in the end? This second edition of Four Views on Hell, featuring all new contributors, highlights why the church still needs to wrestle with the doctrine of hell. In the familiar counterpoints format, four leading scholars introduce us to the current views on eternal judgment, with particular attention being given to the new voices that have entered the debate. The interactive nature of the volume allows the reader to reflect on the strengths and weaknesses of each view and come to an informed conclusion.
Eternal conscious torment / Denny Burk -- Responses / John G. Stackhouse, Robin A. Parry, Jerry L. Walls -- Terminal punishment / John G. Stackhouse -- Responses / Denny Burk, Robin A. Parry, Jerry L. Walls -- A universalist view / Robin A. Parry -- Responses / Denny Burk, John G. Stackhouse, Jerry L. Walls -- Hell and purgatory / Jerry L. Walls -- Responses / Denny Burk, John G. Stackhouse, Robin A. Parry.
Includes bibliographical references and indexes.
Keywords: Hell -- Christianity; Hell -- Christianity